Coloniality : from Latin America to Africa ? - (:unkn) unknown (My University, 2025)
Michel Cahen is a historian of Portuguese colonialism, whose focus has been on the theme of coloniality over the last twenty years. He recent work includes ?Colonialité: Plaidoyer pour la précision d'un concept? Karthala Editions (Paris, May 2024), providing an interpretation of the concept and its issues, in a critical dialogue with different authors, mainly South American decolonial theorists. He particularly emphasizes the diversity of ?regimes of coloniality,? linked to different history of colonial and post-colonial experiences, which, in his view, should be differentiated. Mame-Penda Ba and Philippe Lavigne Delville have interviewed him.
Keywords: African Research